(untitled) (Boston, MA, 2008)
International Business: The Challenge of Global Competition, 10th Edition, by Ball, McCulloch, Geringer, Minor and McNett continues to be the most objective and thorough treatment of International Business available for students. Enriched with maps, photos, and the most up-to-date world data, this text boasts the collective expertise of five authors with firsthand international business experience, specializing in international management, finance, law, global strategy, and marketing. A claim no other text can make. In addition, each new copy of International Business, 10e includes access to CESIM. An interactive IB simulation developed for industry professionals. Ball, et al is the only textbook on the market which features access to CESIM. Only Ball, McCulloch, Geringer, Minor and McNett can offer a complete view of International Business as diverse as the backgrounds of business students.
Keywords: International economic relations,International business enterprises,International business enterprises